THE ADPF 347 AND THE SYSTEM OF PRECEDENTS (CIPEEX, 2026)
This article explores the relationship between ADPF 347, binding precedents, and structural adjudication. It proceeds from the premise that Article 927 of the 2015 Brazilian Code of Civil Procedure inaugurated a system of normative precedents which, while oriented toward legal stability and coherence, must simultaneously accommodate the flexibility and forward-looking dimension demanded by structural litigation. The research adopts a qualitative methodology, grounded in literature review, statutory analysis, and examination of rulings of the Federal Supreme Court. The analysis demonstrates that ADPF 347 designated the Brazilian prison system as a “state of unconstitutional affairs,” thereby introducing into domestic constitutional law a comparative technique of systemic intervention, and that Collective Habeas Corpus 143.641/SP reinforced this trajectory by employing structural parameters to protect the liberty of pregnant women and mothers of children under twelve. The article concludes that prospectivity, far from weakening the binding force of precedents, constitutes a crucial condition of their effectiveness, enabling constitutional adjudication to function as an instrument of social transformation in contexts of systemic rights violations.
Keywords: Precedents; Structural Injunctions; ADPF 347; Procedural Techniques